MEDIATION EFFECT OF LEADERSHIP STYLE ON THE IMPACT OF ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE - Rutan Gunawan, Toto; C. Tarumingkeng, Rudy; Saparso, Saparso (RADJA PUBLIKA, 2022)
This study examines the encouragement provided by organizational support in improving the performance of employees at PT. Maybank Finance Indonesia. This study uses a quantitative descriptive method. When collecting the required data, the researcher will distribute questionnaires to the research samples. Related to this, the population of this study is employees of PT. Maybank Indonesia Finance as of January 2021 who has worked in the company for a minimum of five years and while the sample of this research is employees of PT Maybank Indonesia Finance who have worked for a minimum of five years, which is based on calculations carried out with the formula following the guidelines for determining the sample in Structural Equation Modeling is 120 samples. After getting responses from 120 samples, the researcher will recapitulate the data from the respondents. After that, the researcher will analyze the research data using the Structural Equation. The results showed that organizational support affected leadership style, while leadership style did not affect employee performance. In addition, this study also proves that organizational support can improve employee performance, while leadership style as a mediating variable cannot mediate the effect of organizational support on employee performance.